2017
DOI: 10.1136/bmjopen-2016-014609
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of latent TB infection and TB disease among adolescents in high TB burden countries in Africa: a systematic review protocol

Abstract: IntroductionAlmost a third of the world population has latent tuberculosis (TB) infection (LTBI), ∼10 million of whom develop TB disease annually, despite existence of effective, but lengthy, preventive and curative drug regimens. Although adolescents appear to have a very high force of LTBI, their reported incidence of TB disease is less than that of their corresponding general population. The few available studies on adolescent TB infection and disease prevalence are not sufficient to address the apparent di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Further, the individuals with the lowest TB risk are those born in a town and move to a rural area. These findings are consistent with TB exposure nearing ~ 90% by 25-30 years old (13), with transmission occurring via community contacts during adolescence and adulthood. We hypothesize that those born in towns who later moved to a rural area benefit from both BCG vaccination and decreased adult exposure thereby overall decreasing their odds of TB.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Further, the individuals with the lowest TB risk are those born in a town and move to a rural area. These findings are consistent with TB exposure nearing ~ 90% by 25-30 years old (13), with transmission occurring via community contacts during adolescence and adulthood. We hypothesize that those born in towns who later moved to a rural area benefit from both BCG vaccination and decreased adult exposure thereby overall decreasing their odds of TB.…”
Section: Discussionsupporting
confidence: 85%
“…Controls are patients with suspected TB who have a negative GeneXpert Ultra result and have no history of active pulmonary TB at the time of study enrollment and are largely assumed to be latently infected with M.tb (LTBI). A majority of the population in high TB burden South African suburbs are LTBI, 88% by ages 31-35 (12,13) and studies have consistently shown LTBI in South Africa to be above 75% by age 25, increasing across adulthood (14). Our population-control design relies on population-wide TB exposure, as traditional screening methods, tuberculin skin test (TST) and interferon-gamma release assay (IGRA; e.g., QuantiFERON), are limited both in the concordance and positive predictive value (29,30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To find LTBI-related research articles, we reviewed previous systematic reviews on LTBI to define our search terms [9,10]. We then searched the Web of Science™ (Clarivate Analytics) with the search terms ("latent tuberculosis" OR "LTBI" OR "latent TB") entered under the Topic search field, which searches Title, Abstract, Author Keywords, and Keyword Plus fields [11].…”
Section: Search Terms Data Source and Study Periodmentioning
confidence: 99%
“…Reported adolescent all-TB disease rates (both microbiologically-confirmed and clinically diagnosed) in high TB burden countries in Africa range between 180-679 per 100,000 (2002-2013): [23] 210-341 cases per 100,000 in three South African studies (2002-2013); [24]- [26] 180 cases per 100,000 in one Ugandan study (2009-2011); [27] and 679 cases per 100,000 in one Kenyan study (2010). [28] The relatively lower adolescent TB disease prevalence of 210 cases per 100,000 in the Marais et al South African study [24] could be explained in part by the younger study participants (10-14 years) as compared to the other two South African studies that recruited adolescents aged 10-19 years old.…”
Section: Plos Onementioning
confidence: 99%